HUMANITARIAN NARRATIVE AND POSTHUMANIST CRITIQUE: DAVE EGGERS'S "WHAT IS THE WHAT" - PEEK, MICHELLE (Biography (Honolulu), 2012)
Dave Eggers's What Is the What is the fictionalized real-life story of Valentino Achak Deng, one of Sudan's "Lost Boys." Critical of a rhetoric of rescue and promise, the novel questions humanitarianism and the prescriptive, colonial, and even racist undertones of its humanism, while at the same time sustaining the value of a humanist language of rights in humanitarian life writing.